The Relationship Of Mother’s Knowledge And Educational Level With Triple Elimination Examination - Irya, Nada Amelinda; Bobby Indra Utama; Erda Mutiara Halida; Rauza Sukma Rita; Fitrayeni; Laila (Fakultas Kedokteran Universitas Andalas, 2024)
Introduction: Triple elimination examination can protect mothers and babies from diseases that are transmitted from mother to fetus, namely HIV, Hepatitis B, and Syphilis. Objective: This research aims to determine the relationship between the knowledge and education level of pregnant women and triple elimination examination visits at the Ophir Community Health Center, West Pasaman Regency. Methods: The research design uses analytical research with a cross-sectional method. The population of all pregnant women in the third trimester at the Ophir Community Health Center, West Pasaman Regency in 2023. The total sample was 57 pregnant women taken by total sampling. The data used is primary data using interview and observation methods. The instrument uses a questionnaire sheet. Results: Based on the p-value of the relationship between maternal knowledge and triple elimination examination visits, the p-value was 0.000 (p<0.05). Then, based on the p-value of the relationship between maternal education level and triple elimination examination visits, the result was a p-value of 0.000 (p<0.05). Conclusion: The relationship between knowledge and maternal education level with triple elimination examination visits at the Ophir Community Health Center, West Pasaman Regency.